A carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3, its preparation method, and its application in potassium-sulfur batteries.

CN122950458APending Publication Date: 2026-10-20HEBEI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611416346.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

本发明通过在三维氮掺杂碳纳米纤维材料中引入Fe-N4单原子和KZr2(PO4)3纳米颗粒,并包覆氟化碳保护层,解决了钾金属负极面临的枝晶生长、体积膨胀和界面副反应问题,显著提升了钾硫电池的可逆比容量、倍率性能和循环稳定性

Benefits of technology

[0053]综上所述,本发明公开了一种铁单原子/KZr2(PO4)3共修饰的碳基复合材料,该材料以三维互连的氮掺杂碳纳米纤维多孔骨架为基体,碳基体中分散有Fe-N4单原子位点,纤维表面及孔道内负载KZr2(PO4)3钾离子快导纳米颗粒,外表面具有氟化碳保护层,孔道内填充金属钾。其制备方法包括配制含聚丙烯腈、乙酰丙酮铁和硝酸氧锆的纺丝液,经静电纺丝、高速剪切分散、冷冻干燥、预氧化碳化、原位磷酸盐化、四氟化碳等离子体氟化及熔融钾浸渗。该材料通过 Fe-N4单原子位点引导钾均匀成核、KZr2(PO4)3纳米颗粒加速钾离子传输、氟化碳层稳定电极界面以及多孔骨架缓冲体积变化,有效抑制了钾枝晶生长和多硫化物穿梭,作为钾硫电池负极可促使正极材料实现较高的可逆容量、良好的倍率性能和循环稳定性,在高能量密度钾硫电池中具有应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of battery materials technology, specifically disclosing a carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3, its preparation method, and its application in potassium-sulfur batteries. The material uses a three-dimensionally interconnected nitrogen-doped carbon nanofiber porous framework as its matrix, with Fe-N4 single-atom sites dispersed within the carbon matrix. KZr2(PO4)3 potassium ion-conducting nanoparticles are loaded on the fiber surface and within the pores. A fluorinated carbon protective layer covers the outer surface, and metallic potassium is filled within the pores. This material effectively suppresses potassium dendrite growth through Fe-N4 single-atom sites guiding uniform potassium nucleation, KZr2(PO4)3 nanoparticles accelerating potassium ion transport, the fluorinated carbon layer stabilizing the electrode interface, and the porous framework buffering volume changes. As a negative electrode in potassium-sulfur batteries, it exhibits high reversible capacity, good rate performance, and cycle stability, showing promising application prospects in high-energy-density potassium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and in particular to a carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3, its preparation method, and its application in potassium-sulfur batteries. Background Technology

[0002] Potassium-sulfur batteries possess advantages such as abundant sulfur resources, high theoretical energy density, and low cost, making them promising candidates for large-scale energy storage. A typical potassium-sulfur battery comprises a sulfur cathode, a potassium metallic anode, a non-aqueous electrolyte, and a separator. During charge and discharge, soluble potassium polysulfide intermediates readily form on the sulfur cathode side. These intermediates migrate to the anode side and react chemically with the potassium metallic oxide, leading to the consumption of active potassium and continuous rupture and reconstruction of the interfacial membrane.

[0003] Furthermore, potassium metal exhibits high chemical reactivity, which can easily lead to problems such as localized current density concentration, uneven deposition, and dendrite growth during deposition / stripping. Simultaneously, changes in the morphology of potassium metal deposition can cause interfacial film rupture and continuous electrolyte consumption, resulting in increased polarization, decreased coulombic efficiency, and reduced cycle life. Therefore, there is an urgent need to construct a composite potassium metal anode that combines uniform potassium deposition capability, ion transport capability, volume change buffering capability, and interfacial stability capability to enable sulfur cathodes to achieve excellent potassium storage performance.

[0004] To improve the cycling stability of potassium metal anodes, a common approach is to use a three-dimensional porous framework as a potassium metal carrier to increase the reaction area, reduce local current density, and provide buffer space for volume changes. However, ordinary carbon materials have limited wettability and affinity for potassium metal, and the open porous structure may increase the contact area between the electrolyte and potassium polysulfides with potassium metal. Therefore, it is still necessary to synergistically regulate the nucleation sites, local ion transport environment, and surface protective layer of the three-dimensional carbon framework. Summary of the Invention

[0005] To address the aforementioned problems of existing potassium-sulfur batteries, this invention provides a carbon-based composite material co-modified with iron single atoms and KZr2(PO4)3, its preparation method, and its application in potassium-sulfur batteries. This invention solves the problems of dendrite growth, volume expansion, and interfacial side reactions faced by potassium metal anodes by introducing Fe-N4 single atoms and KZr2(PO4)3 nanoparticles into three-dimensional nitrogen-doped carbon nanofiber materials and coating them with a fluorinated carbon protective layer. This significantly improves the reversible specific capacity, rate performance, and cycle stability of potassium-sulfur batteries.

[0006] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows: In a first aspect, the present invention provides a carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3, comprising a three-dimensionally interconnected porous framework of nitrogen-doped carbon nanofibers, wherein Fe-N4 single atoms are dispersed in the carbon matrix of the nitrogen-doped carbon nanofibers; KZr2(PO4)3 nanoparticles are loaded on the surface and in the pores of the nitrogen-doped carbon nanofibers; and the outer surface of the nitrogen-doped carbon nanofibers is coated with a fluorinated carbon protective layer; and the pores of the porous framework of the nitrogen-doped carbon nanofibers are further filled with metallic potassium.

[0007] Compared with the prior art, the iron single-atom / KZr2(PO4)3 co-modified carbon-based composite material provided by the present invention has the following beneficial effects: The three-dimensional interconnected carbon nanofiber framework provides a continuous electron transport network and internal pore space, reducing the local current density during potassium deposition / exfoliation and buffering potassium morphology changes. The uniformly anchored Fe-N4 single-atom sites in the carbon framework serve as atomically dispersed potassium-loving nucleation sites, improving the affinity of the carbon framework for potassium, reducing potassium nucleation overpotential, and promoting more uniform potassium deposition within the three-dimensional framework. KZr2(PO4)3 nanoparticles are fast potassium-conducting phases, and their uniform distribution within the carbon framework constructs continuous potassium-ion migration channels, which is beneficial for improving the migration rate of potassium ions inside the electrode and mitigating the slow solid-phase diffusion kinetics caused by the large radius of potassium ions. The fluorinated carbon protective layer on the outer surface can induce the formation of a stable artificial solid electrolyte interface film rich in KF during battery cycling, thereby reducing the direct contact between the electrolyte and soluble potassium polysulfide with potassium and mitigating interfacial side reactions.

[0008] The synergistic effect of the above functional components enables the composite material to exhibit high reversible specific capacity, good rate performance and cycle stability when used as the anode of potassium-sulfur batteries, providing a reliable anode material preparation approach for constructing high energy density and long life potassium-sulfur batteries.

[0009] Secondly, the present invention provides a method for preparing a carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3, comprising the following steps: Step a: Polyacrylonitrile, pore-forming agent, iron acetylacetone and zirconium oxynitrate are added to an organic solvent and mixed evenly to obtain a spinning solution; the spinning solution is electrospun to obtain a nanofiber membrane. Step b: Disperse the nanofiber membrane in an alcohol-water solution and shear it at high speed to obtain a fiber slurry; freeze-dry the fiber slurry to obtain a three-dimensional fiber aerogel. Step c: The three-dimensional fiber aerogel is subjected to pre-oxidation and carbonization treatments in sequence to obtain nitrogen-doped carbon nanofibers; Step d: The nitrogen-doped carbon nanofibers are added to a mixed solution containing potassium source, phosphorus source and citric acid for vacuum impregnation, dried and then heat-treated under an inert atmosphere to cause Zr to undergo an in-situ phosphate reaction with potassium source and phosphate to obtain nitrogen-doped carbon nanofibers loaded with KZr2(PO4)3. Step e: The nitrogen-doped carbon nanofibers loaded with KZr2(PO4)3 are placed in a plasma reaction chamber and subjected to plasma treatment with carbon tetrafluoride as a fluorine source to form a fluorinated carbon protective layer on the surface, thereby obtaining a three-dimensional carbon-based support. Step f: Then, under an inert atmosphere, molten potassium metal is brought into contact with the three-dimensional carbon-based support, allowing the molten potassium to penetrate into its porous framework, resulting in a carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3.

[0010] Compared to existing technologies, the method for preparing iron single-atom / KZr2(PO4)3 co-modified carbon-based composite materials provided by this invention achieves molecular-level uniform dispersion of iron and zirconium sources within the polymer matrix from the raw material stage by introducing iron acetylacetonate and zirconium oxynitrate as liquid-phase precursors into the polyacrylonitrile spinning solution. During the subsequent carbonization process, the organic ligands of iron acetylacetonate effectively isolate iron atoms, inhibiting their migration and aggregation at high temperatures, thereby forming atomically dispersed Fe-N4 single-atom sites in situ on the nitrogen-doped carbon framework. The decomposition of zirconium oxynitrate during subsequent carbonization, accompanied by gas escape and volume shrinkage, leaves nanoscale voids in situ within the hard carbon wall. These voids can buffer the volume expansion during potassium insertion / extraction.

[0011] The carbonized carbon fiber aerogel was vacuum impregnated in a solution containing potassium, phosphorus, and citric acid. The negative pressure environment facilitated the full penetration of the solution into the three-dimensional channels. Citric acid, acting as a ligand, coordinated with the exposed Zr centers in the carbon skeleton, ensuring uniform dispersion of potassium and phosphorus sources around the Zr species. After heat treatment under an inert atmosphere, the highly reactive Zr species reacted in situ with the potassium and phosphorus sources, generating KZr2(PO4)3 nanoparticles tightly bound to the carbon skeleton. This avoided the problems of uneven distribution and weak interfacial bonding common in direct particle addition methods. Subsequently, plasma treatment was performed using carbon tetrafluoride as the fluorine source, introducing a fluorinated carbon protective layer onto the material surface. This protective layer can participate in the formation of a stable solid electrolyte interface layer rich in KF during electrochemical cycling, improving the uniformity of interfacial ion transport and structural stability. Furthermore, it acts as a physical barrier, effectively preventing the penetration and chemical corrosion of soluble potassium polysulfides into the potassium metal interface.

[0012] Finally, the surface-fluorinated carbon-based host material is brought into contact with molten potassium. The molten potassium spontaneously infiltrates into the pores of the three-dimensional porous framework under capillary action. After cooling, the carbon-based composite material is obtained. This carbon-based composite material can be directly used as the negative electrode of potassium-sulfur batteries after subsequent pressing.

[0013] In some embodiments of the present invention, in step a, the pore-forming agent is at least one of polyvinylpyrrolidone, polymethyl methacrylate, polyethylene glycol, or polystyrene.

[0014] The aforementioned pore-forming agent can be decomposed and released during the carbonization process, forming abundant mesopores and macropores in situ inside and on the surface of the fiber, significantly increasing the specific surface area and porosity of the material, and providing sufficient interfacial space for subsequent exposure of active sites and ion transport.

[0015] In some embodiments of the present invention, in step a, the organic solvent is N,N-dimethylformamide.

[0016] In some embodiments of the present invention, in step a, the mass ratio of the polyacrylonitrile to the pore-forming agent is 3:1 to 4:1.

[0017] In some embodiments of the present invention, in step a, the amount of iron acetylacetone added is 1% to 10% of the mass of polyacrylonitrile.

[0018] By controlling the amount of iron acetylacetone added within the above-mentioned range, the thermal agglomeration of iron atoms during carbonization can be effectively suppressed, ensuring that iron is anchored in the nitrogen-doped carbon framework in an atomically dispersed form, thereby fully leveraging its function of inducing uniform potassium nucleation. If the amount added is less than 1%, it is difficult to form sufficiently dense Fe-N4 single-atom potassium-loving nucleation sites in the carbon framework, and its effect on regulating the uniformity of potassium deposition is limited. If the amount added is greater than 10%, the excess iron species are prone to migration and agglomeration during high-temperature carbonization, forming iron or iron carbide nanoparticles, which may also block pores and weaken the conductivity continuity of the carbon framework.

[0019] In some embodiments of the present invention, in step a, the amount of zirconium oxynitrate added is 2% to 15% of the mass of polyacrylonitrile.

[0020] Within the above dosage range, zirconium oxynitrate is uniformly dispersed in the polyacrylonitrile matrix at the molecular level. During the subsequent carbonization process, it can not only form sufficient buffer cavities in situ inside the fiber, but also provide uniform and highly reactive zirconium sites for the subsequent in-situ phosphate reaction, ensuring the high dispersibility and interfacial bonding strength of KZr2(PO4)3 nanoparticles in the carbon skeleton.

[0021] In some embodiments of the present invention, in step a, the mass concentration of polyacrylonitrile in the spinning solution is 8% to 15%.

[0022] In some embodiments of the present invention, in step a, the mixing temperature is 60°C to 80°C, and the mixing time is 6h to 12h.

[0023] In some embodiments of the present invention, in step a, the voltage of the electrospinning is 15kV~25kV, the receiving distance is 15cm~20cm, and the advancing speed is 0.5mL / h~2mL / h.

[0024] In some embodiments of the present invention, in step b, the nanofiber membrane is first cut into pieces with an average fragment size of 0.5 mm to 5 mm before dispersion.

[0025] In some embodiments of the present invention, in step b, the alcohol-water solution is a mixed solution of deionized water and tert-butanol with a volume ratio of 1:1 to 1:4.

[0026] In some embodiments of the present invention, in step b, the mass-to-volume ratio of the nanofiber membrane to the alcohol-water solution is 1g:100mL to 1g:300mL.

[0027] In some embodiments of the present invention, in step b, the rotational speed of the high-speed shearing is 8000 rpm to 15000 rpm, and the high-speed shearing time is 20 min to 60 min.

[0028] Nanofiber membranes were dispersed in an alcohol-water solution and subjected to high-speed shearing to form a uniform fiber slurry. After freeze-drying, the fibers randomly overlapped during the ice crystal growth process, forming a three-dimensional interconnected fiber aerogel precursor, which laid the foundation for obtaining a hierarchical porous structure with continuous electronic pathways and sufficient buffer space.

[0029] In some embodiments of the present invention, step b, the specific steps of freeze drying include: first freezing at -20℃ to -80℃ for 4h to 12h, and then vacuum freezing at -50℃ to -80℃ and 5Pa to 15Pa for 24h to 48h.

[0030] The fiber slurry is first frozen at -20℃ to -80℃ for 4 to 12 hours, allowing the solvent to fully crystallize and fixing the uniformly dispersed fiber network in the liquid state within a solid ice crystal template. This prevents pore shrinkage and structural collapse caused by capillary forces during drying. Subsequently, it is dried under high vacuum conditions of -50℃ to -80℃ and 5 to 15 Pa for 24 to 48 hours. The ice crystals are directly sublimated and removed, while the fiber skeleton is completely preserved in an environment without liquid phase surface tension, ultimately forming an aerogel precursor with high porosity and a three-dimensional interconnected network structure. This structure provides an ideal skeletal basis for constructing a hollow conductive network and accommodating potassium metal deposition in the subsequent carbonization stage.

[0031] In some embodiments of the present invention, in step c, the pre-oxidation temperature is 220℃~280℃, and the pre-oxidation time is 2h~3h.

[0032] Within the aforementioned temperature and time, the pre-oxidation reaction is uniform and controllable, and the fiber interior is fully cyclized without excessive oxidation, providing an ideal intermediate structure for the formation of a structurally complete hollow nitrogen-doped carbon fiber skeleton during the carbonization stage.

[0033] In some embodiments of the present invention, in step c, the carbonization temperature is 900℃~1000℃ and the carbonization time is 2h~3h.

[0034] The aforementioned carbonization conditions allow for the complete carbonization of polyacrylonitrile, forming a nitrogen-doped carbon framework with good electrical conductivity. Simultaneously, iron acetylacetone decomposes and coordinates with nitrogen in the framework to form Fe-N4 single-atom sites, while zirconium oxynitrate is transformed into highly reactive Zr species. Too low a temperature leads to incomplete carbonization, poor conductivity, and insufficient single-atom coordination; too high a temperature easily causes iron atom migration and aggregation, nitrogen loss, and excessive shrinkage of the carbon framework.

[0035] In some embodiments of the present invention, in step d, the mixed solution is an aqueous solution containing 0.05 mol / L to 0.20 mol / L potassium dihydrogen phosphate and 0.02 mol / L to 0.10 mol / L citric acid; the mass-to-volume ratio of the nitrogen-doped carbon nanofibers to the mixed solution is 1 g:50 mL to 1 g:200 mL.

[0036] In some embodiments of the present invention, in step d, the temperature of the vacuum impregnation is 20°C to 30°C, the vacuum degree is 0.08MPa to 0.10MPa, and the impregnation time is 10min to 40min.

[0037] In some embodiments of the present invention, in step d, the temperature of the heat treatment is 500℃~600℃, and the heat treatment time is 2h~4h.

[0038] Within the aforementioned temperature range, Zr species can undergo in-situ solid-phase reactions with phosphorus and potassium sources generated from the decomposition of potassium dihydrogen phosphate and citric acid to generate KZr2(PO4)3 nanoparticles with good crystallinity, thereby providing an efficient potassium ion transport pathway that runs through the framework while maintaining the integrity of the three-dimensional conductive network structure.

[0039] In some embodiments of the present invention, in step d, the drying is carried out by vacuum drying, with a vacuum drying temperature of 60℃~80℃, a vacuum degree of 0.08MPa~0.10MPa, and a vacuum drying time of 6h~12h.

[0040] It should be noted that the inert atmosphere mentioned in step d is provided by an inert gas, which can be a conventional inert gas in the art, such as argon or nitrogen.

[0041] In some embodiments of the present invention, in step e, the power of the plasma treatment is 80W~150W, the treatment time is 10min~30min, and the flow rate of the carbon tetrafluoride is 10sccm~40sccm.

[0042] It should be noted that in step e, during the plasma treatment process, the sample temperature is kept below 60°C by circulating cooling water, and the sample stage temperature is controlled at 20°C to 40°C.

[0043] In some embodiments of the present invention, in step f, the mass ratio of the molten potassium to the three-dimensional carbon-based support is 1.5:1 to 4:1.

[0044] Thirdly, the present invention also provides a negative electrode comprising the above-mentioned iron single atom / KZr2(PO4)3 co-modified carbon-based composite material.

[0045] In some embodiments, the negative electrode further includes a current collector, on which the carbon-based composite material is disposed. The current collector may be a conventional negative electrode current collector in the art, such as copper foil, aluminum foil, nickel foil, carbon paper, or carbon cloth. The carbon-based composite material may be bonded to the current collector by coating, rolling, or direct growth.

[0046] In other embodiments, the carbon-based composite material is a self-supporting aerogel sheet or a rolled sheet, possessing sufficient mechanical strength and conductivity to be used directly as a negative electrode without additional current collector, thus improving the overall energy density of the battery. Depending on the manufacturing process, a binder and a conductive agent may also be added to the negative electrode. The binder can be one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, or polyacrylic acid, and the conductive agent can be one or more of superconducting carbon black, acetylene black, carbon nanotubes, or graphene. This pre-potassium-modified composite negative electrode can be directly used in potassium-sulfur batteries. Metallic potassium is in close contact with the inner surface of the three-dimensional framework, and during cycling, potassium is confined within the porous framework for deposition and stripping, thereby contributing to high coulombic efficiency and long cycle life in potassium-sulfur batteries.

[0047] Specifically, the thickness of the negative electrode sheet can be 100μm~200μm.

[0048] Fourthly, the present invention also provides a potassium-sulfur battery, comprising the above-mentioned iron single atom / KZr2(PO4)3 co-modified carbon-based composite material or the above-mentioned negative electrode.

[0049] The potassium-sulfur battery further includes a positive electrode, an electrolyte, and a separator. The active material of the positive electrode is sulfur or a sulfur-containing material. The electrolyte is a non-aqueous electrolyte formed by dissolving a potassium salt electrolyte in an organic solvent. The potassium salt can be one or more of potassium bis(fluorosulfonyl)imide, potassium bis(trifluoromethanesulfonyl)imide, and potassium hexafluorophosphate. The organic solvent can be one or more of ethylene glycol dimethyl ether, ethylene carbonate, propylene carbonate, or dimethyl carbonate. In some embodiments, film-forming additives or other functional additives may be added to the electrolyte to further stabilize the electrode interface, such as fluoroethylene carbonate, potassium nitrate, or polysulfides.

[0050] The diaphragm can be made of conventional diaphragm materials in this field, such as glass fiber filter paper, polypropylene microporous membrane, polyethylene microporous membrane, or polypropylene / polyethylene composite microporous membrane.

[0051] In the aforementioned potassium-sulfur battery, the carbon-based composite material of this invention serves as the negative electrode. Its three-dimensional interconnected porous framework provides ample space and a continuous conductive network for potassium deposition and stripping. Fe-N4 single-atom sites guide uniform potassium nucleation and catalyze polysulfide conversion. KZr2(PO4)3 fast-conducting nanoparticles accelerate potassium ion transport, and a fluorinated carbon protective layer stabilizes the negative electrode interface and inhibits potassium polysulfide corrosion. The synergistic effect of these structures enables the potassium-sulfur battery to exhibit high reversible specific capacity, good rate performance, and long cycle life during cycling.

[0052] Fifthly, the present invention also provides a battery module, including the potassium-sulfur battery described above.

[0053] In summary, this invention discloses a carbon-based composite material co-modified with iron single atoms and KZr2(PO4)3. This material uses a three-dimensionally interconnected nitrogen-doped carbon nanofiber porous framework as its matrix, with Fe-N4 single-atom sites dispersed within the carbon matrix. KZr2(PO4)3 potassium ion fast-conducting nanoparticles are loaded on the fiber surface and within the pores. The outer surface has a fluorinated carbon protective layer, and the pores are filled with metallic potassium. The preparation method includes preparing a spinning solution containing polyacrylonitrile, iron acetylacetone, and zirconium oxynitrate, followed by electrospinning, high-speed shear dispersion, freeze-drying, pre-oxidation carbonization, in-situ phosphate treatment, carbon tetrafluoride plasma fluorination, and molten potassium infiltration. This material effectively suppresses potassium dendrite growth and polysulfide shuttle by guiding uniform potassium nucleation through Fe-N4 single-atom sites, accelerating potassium ion transport through KZr2(PO4)3 nanoparticles, stabilizing the electrode interface with a fluorinated carbon layer, and buffering volume changes with a porous framework. As a negative electrode for potassium-sulfur batteries, it can promote the achievement of high reversible capacity, good rate performance, and cycle stability in positive electrode materials, and has promising applications in high-energy-density potassium-sulfur batteries. Attached Figure Description

[0054] Figure 1The Fe K-side Fourier transform EXAFS spectrum of the FeSA-KZP / F-CNF sample prepared in Example 2 of this invention; Figure 2 The image shows the aberration-corrected HAADF-STEM image of the FeSA-KZP / F-CNF sample prepared in Example 2 of this invention. Figure 3 HAADF-STEM image and elemental distribution map of the FeSA-KZP / F-CNF sample prepared in Example 2 of this invention; Figure 4 The XPS spectrum of the F 1s of the FeSA-KZP / F-CNF sample prepared in Example 2 of this invention; Figure 5 The N 1s XPS spectrum of the FeSA-KZP / F-CNF sample prepared in Example 2 of this invention; Figure 6 The charge-discharge curves of the positive electrode material at a current density of 5 A / g when the FeSA-KZP / F-CNF sample prepared in Example 2 of this invention is used as the negative electrode; Figure 7 The graph shows the positive electrode material after 1000 cycles at a current density of 5 A / g when the FeSA-KZP / F-CNF sample prepared in Example 2 of this invention is used as the negative electrode. Detailed Implementation

[0055] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0056] To better illustrate the present invention, further examples are provided below.

[0057] Example 1 A method for preparing a carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3 includes the following steps: Step 1: Add 1.0g polyacrylonitrile, 0.33g polyvinylpyrrolidone, 0.01g iron acetylacetonate and 0.02g zirconium oxynitrate to 10mL N,N-dimethylformamide and stir at 60℃ for 12h to obtain spinning solution.

[0058] Step 2: Electrospin the obtained spinning solution with a spinning voltage of 20 kV, a receiving distance of 16 cm, and a feed rate of 0.5 mL / h to obtain a polymer nanofiber membrane.

[0059] Step 3: After cutting the above nanofiber membrane into pieces with an average fragment size of 0.5 mm, disperse the nanofiber membrane and the mixed solvent in a ratio of 1 g: 200 mL in 100 mL of deionized water and 100 mL of tert-butanol mixed solvent. Then, shear the mixture at high speed at 12000 rpm for 30 min to obtain a fiber slurry. Pour the fiber slurry into a cylindrical mold and freeze it at -20℃ for 12 h. Then, freeze-dry it at -50℃ and 5 Pa vacuum for 48 h to obtain a three-dimensional fiber aerogel.

[0060] Step 4: Pre-oxidize the three-dimensional fiber aerogel in air at 250°C for 2 hours, and then carbonize it at 950°C for 2 hours under an argon atmosphere to obtain nitrogen-doped carbon nanofiber aerogel.

[0061] Step 5: The obtained nitrogen-doped carbon nanofiber aerogel was immersed in a mixed solution containing 0.1 mol / L potassium dihydrogen phosphate and 0.05 mol / L citric acid at a ratio of 1 g: 60 mL. The aerogel was vacuum-impregnated for 30 min at 20 °C and 0.10 MPa. The impregnated carbon aerogel was then vacuum-dried for 6 h at 60 °C and 0.08 MPa, and then treated at 550 °C for 3 h under an argon atmosphere to obtain a composite carbon aerogel loaded with KZr2(PO4)3.

[0062] Step 6: Place the above-mentioned composite carbon aerogel in a plasma reaction chamber, use carbon tetrafluoride as the fluorine source, and process it at 100W power for 15 minutes. The carbon tetrafluoride flow rate is 30 sccm, the sample stage temperature is 40℃, and the sample temperature is kept below 60℃ by circulating water cooling during the process, thus obtaining FeSA-KZP / F-CNF carbon-based framework material with a carbon tetrafluoride protective layer.

[0063] Step 7: In an argon glove box, metallic potassium is heated to 90°C to form molten potassium. The molten potassium is then dropped onto the surface of the FeSA-KZP / F-CNF carbon-based framework material. The mass ratio of molten potassium to FeSA-KZP / F-CNF carbon-based framework material is 2:1. The contact is maintained for 20 minutes to allow the molten potassium to spontaneously infuse into the carbon aerogel. After cooling, the aerogel is rolled into a composite potassium metal anode with a thickness of 150 μm, denoted as K@FeSA-KZP / F-CNF composite anode material.

[0064] Example 2 A method for preparing a carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3 includes the following steps: Step 1: Add 1.0g polyacrylonitrile, 0.25g polymethyl methacrylate, 0.1g iron acetylacetone and 0.1g zirconium oxynitrate to 9mL N,N-dimethylformamide and stir at 70℃ for 10h to obtain spinning solution.

[0065] Step 2: Electrospin the obtained spinning solution with a spinning voltage of 15 kV, a receiving distance of 15 cm, and a feed rate of 0.8 mL / h to obtain a polymer nanofiber membrane.

[0066] Step 3: After cutting the above nanofiber membrane into pieces with an average fragment size of 1 mm, disperse it in a mixed solvent of 20 mL deionized water and 80 mL tert-butanol at a ratio of 1 g: 100 mL. Then, shear it at high speed at 10,000 rpm for 40 min to obtain a fiber slurry. Pour the fiber slurry into a cylindrical mold and freeze it at -60℃ for 6 h. Then, freeze-dry it at -70℃ and 10 Pa vacuum for 24 h to obtain a three-dimensional fiber aerogel.

[0067] Step 4: Pre-oxidize the three-dimensional fiber aerogel in air at 260℃ for 2 h, and then carbonize it at 900℃ for 3 h under an argon atmosphere to obtain nitrogen-doped carbon nanofiber aerogel.

[0068] Step 5: The obtained nitrogen-doped carbon nanofiber aerogel was immersed in a mixed solution containing 0.05 mol / L potassium dihydrogen phosphate and 0.02 mol / L citric acid at a ratio of 1 g: 100 mL. The aerogel was vacuum-impregnated for 20 min at 25 °C and 0.10 MPa. The impregnated carbon aerogel was then vacuum-dried for 8 h at 70 °C and 0.09 MPa, and then treated at 500 °C for 4 h under an argon atmosphere to obtain a composite carbon aerogel loaded with KZr2(PO4)3.

[0069] Step 6: Place the above-mentioned composite carbon aerogel in a plasma reaction chamber, use carbon tetrafluoride as the fluorine source, and treat it at 80W power for 30 minutes. The carbon tetrafluoride flow rate is 40 sccm, the sample stage temperature is 20℃, and the sample temperature is kept below 60℃ by circulating water cooling during the treatment process, so as to obtain FeSA-KZP / F-CNF carbon-based framework material with a carbon tetrafluoride protective layer.

[0070] Step 7: In an argon glove box, metallic potassium is heated to 90°C to form molten potassium. The molten potassium is then dropped onto the surface of the FeSA-KZP / F-CNF carbon-based framework material. The mass ratio of molten potassium to FeSA-KZP / F-CNF carbon-based framework material is 3:1. The contact is maintained for 15 minutes to allow the molten potassium to spontaneously infuse into the carbon aerogel. After cooling, the material is rolled into a composite potassium metal anode with a thickness of 160 μm, denoted as K@FeSA-KZP / F-CNF composite anode material.

[0071] The Fe K-side Fourier transform EXAFS spectrum of the K@FeSA-KZP / F-CNF composite anode material prepared in this embodiment is shown below. Figure 1As shown in the figure, in the Fe K-side Fourier transform extended X-ray absorption fine structure spectrum of the sample, a characteristic peak belonging to the first coordination shell of Fe-N coordination appears at approximately 1.5 Å, while no characteristic peak of Fe-Fe coordination is observed at approximately 2.2 Å, indicating that iron is dispersed in a single-atom form and mainly coordinated with nitrogen atoms. Fitting analysis shows that the Fe-N coordination number is 3.9, close to a four-coordinate structure, consistent with the coordination configuration of Fe-N4.

[0072] The aberration-corrected HAADF-STEM image of the K@FeSA-KZP / F-CNF composite anode material is shown below. Figure 2 As shown in the figure, the numerous isolated, dispersed, high-contrast bright spots marked with yellow circles correspond to atomically dispersed heavy atom species. Combined with the fitting results of the Fe K-edge extended X-ray absorption fine structure spectrum, the sample exhibits a first coordination shell peak of Fe-N coordination at approximately 1.5 Å, with a fitted Fe-N coordination number of 3.9. Furthermore, no Fe-Fe coordination characteristic peak was detected at approximately 2.2 Å, indicating that the aforementioned high-contrast bright spots are iron single atoms anchored in the nitrogen-doped carbon framework in the form of Fe-N4 coordination, and do not form iron nanoparticles or clusters.

[0073] HAADF-STEM image and elemental distribution diagram of K@FeSA-KZP / F-CNF composite anode material are shown below. Figure 3 As shown, the elemental distribution results indicate that C, N, Fe, Zr, and F are all distributed in the composite carbon aerogel framework. Fe is highly dispersed and uniformly distributed in the nitrogen-doped carbon framework, with no obvious enrichment areas observed. Zr is uniformly distributed and highly overlaps with the distribution areas of C and N, indicating that the zirconium-containing component has achieved uniform loading in the carbon framework. F is mainly distributed on the surface of the framework, confirming that the fluorinated carbon protective layer has been successfully introduced to the material surface.

[0074] The F 1s XPS spectrum of the K@FeSA-KZP / F-CNF composite anode material is shown below. Figure 4 As shown in the figure, characteristic peaks belonging to CF bonds appear in the binding energy range of approximately 685.5–687.0 eV, indicating that fluorinated carbon components were successfully introduced into the surface of carbon nanofibers after tetrafluoride plasma treatment. Simultaneously, characteristic peaks belonging to KF bonds were observed at approximately 683.0–684.0 eV, indicating that KF-containing interfacial species have been formed on the treated surface. These results demonstrate that a fluorine-containing protective layer has been successfully constructed on the material surface, and this protective layer can participate in situ in the formation of a stable solid-state electrolyte interfacial layer rich in KF during subsequent electrochemical cycling.

[0075] The N 1s XPS spectrum of the K@FeSA-KZP / F-CNF composite anode material is shown below. Figure 5As shown in the figure, characteristic peaks belonging to Fe-N coordination bonds appear in the binding energy range of 399.5–400.0 eV, indicating that iron atoms form chemical coordination with nitrogen atoms in the nitrogen-doped carbon framework. Combined with the fitting results of the atomically dispersed iron species observed in the aforementioned aberration-corrected HAADF-STEM image and the Fe K-edge EXAFS spectrum, the successful construction of Fe-N4 single-atom sites in the carbon framework is further confirmed.

[0076] Example 3 A method for preparing a carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3 includes the following steps: Step 1: Add 1.0g polyacrylonitrile, 0.3g polyethylene glycol, 0.08g iron acetylacetone and 0.05g zirconium oxynitrate to 8mL N,N-dimethylformamide and stir at 75℃ for 8h to obtain spinning solution.

[0077] Step 2: Electrospin the obtained spinning solution with a spinning voltage of 18kV, a receiving distance of 17cm, and a feed rate of 1.3mL / h to obtain a polymer nanofiber membrane.

[0078] Step 3: After cutting the above nanofiber membrane into pieces with an average fragment size of 2 mm, disperse the nanofiber membrane in a mixed solvent of 1 g: 300 mL in 100 mL of deionized water and 200 mL of tert-butanol at a ratio of 1 g: 300 mL. Then, shear the mixture at high speed at 8000 rpm for 60 min to obtain a fiber slurry. Pour the fiber slurry into a cylindrical mold and freeze it at -80℃ for 4 h. Then, freeze-dry it at -80℃ and 8 Pa vacuum for 24 h to obtain a three-dimensional fiber aerogel.

[0079] Step 4: Pre-oxidize the three-dimensional fiber aerogel in air at 220℃ for 3 hours, and then carbonize it at 960℃ for 2.5 hours under an argon atmosphere to obtain nitrogen-doped carbon nanofiber aerogel.

[0080] Step 5: The obtained nitrogen-doped carbon nanofiber aerogel was immersed in a mixed solution containing 0.2 mol / L potassium dihydrogen phosphate and 0.1 mol / L citric acid at a ratio of 1 g: 50 mL. The aerogel was vacuum-impregnated at 30 °C and 0.08 MPa for 10 min. The impregnated carbon aerogel was then vacuum-dried at 80 °C and 0.10 MPa for 10 h. Finally, it was treated at 570 °C for 2.5 h under an argon atmosphere to obtain a composite carbon aerogel loaded with KZr2(PO4)3.

[0081] Step 6: Place the above-mentioned composite carbon aerogel in a plasma reaction chamber, use carbon tetrafluoride as the fluorine source, and treat it at 150W power for 10 minutes. The carbon tetrafluoride flow rate is 10 sccm, the sample stage temperature is 30℃, and the sample temperature is kept below 60℃ by circulating water cooling during the treatment process, so as to obtain FeSA-KZP / F-CNF carbon-based framework material with a carbon tetrafluoride protective layer.

[0082] Step 7: In an argon glove box, metallic potassium is heated to 90°C to form molten potassium. The molten potassium is then dropped onto the surface of the FeSA-KZP / F-CNF carbon-based framework material. The mass ratio of molten potassium to FeSA-KZP / F-CNF carbon-based framework material is 4:1. The contact is maintained for 10 minutes to allow the molten potassium to spontaneously infuse into the carbon aerogel. After cooling, the aerogel is rolled into a composite potassium metal anode with a thickness of 100 μm, denoted as K@FeSA-KZP / F-CNF composite anode material.

[0083] Example 4 A method for preparing a carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3 includes the following steps: Step 1: Add 1.0g polyacrylonitrile, 0.28g polystyrene, 0.04g iron acetylacetone and 0.15g zirconium oxynitrate to 12mL N,N-dimethylformamide and stir at 80℃ for 6h to obtain spinning solution.

[0084] Step 2: Electrospin the obtained spinning solution with a spinning voltage of 25 kV, a receiving distance of 20 cm, and a feed rate of 2.0 mL / h to obtain a polymer nanofiber membrane.

[0085] Step 3: After cutting the above nanofiber membrane into pieces with an average fragment size of 5 mm, disperse the nanofiber membrane and mixed solvent in a mixed solvent of 100 mL deionized water and 150 mL tert-butanol at a ratio of 1 g: 250 mL. Then, shear the mixture at high speed at 15000 rpm for 20 min to obtain a fiber slurry. Pour the fiber slurry into a cylindrical mold and freeze it at -50℃ for 5 h. Then, freeze-dry it at -65℃ and 5 Pa vacuum for 30 h to obtain a three-dimensional fiber aerogel.

[0086] Step 4: Pre-oxidize the three-dimensional fiber aerogel in air at 280℃ for 2 hours, and then carbonize it at 1000℃ for 2 hours under an argon atmosphere to obtain nitrogen-doped carbon nanofiber aerogel.

[0087] Step 5: The obtained nitrogen-doped carbon nanofiber aerogel was immersed in a mixed solution containing 0.05 mol / L potassium dihydrogen phosphate and 0.02 mol / L citric acid at a ratio of 1 g: 200 mL. The aerogel was vacuum-impregnated at 25 °C and 0.10 MPa for 40 min. The impregnated carbon aerogel was then vacuum-dried at 75 °C and 0.08 MPa for 12 h, and then treated at 600 °C for 2 h under an argon atmosphere to obtain a composite carbon aerogel loaded with KZr2(PO4)3.

[0088] Step 6: Place the above-mentioned composite carbon aerogel in a plasma reaction chamber, use carbon tetrafluoride as the fluorine source, and process it at 120W power for 20 minutes. The carbon tetrafluoride flow rate is 15 sccm, the sample stage temperature is 30℃, and the sample temperature is kept below 60℃ by circulating water cooling during the process, thus obtaining FeSA-KZP / F-CNF carbon-based framework material with a carbon tetrafluoride protective layer.

[0089] Step 7: In an argon glove box, metallic potassium is heated to 90°C to form molten potassium. The molten potassium is then dropped onto the surface of the FeSA-KZP / F-CNF carbon-based framework material. The mass ratio of molten potassium to FeSA-KZP / F-CNF carbon-based framework material is 1.5:1. The contact is maintained for 30 minutes to allow the molten potassium to spontaneously infuse into the carbon aerogel. After cooling, the material is rolled into a composite potassium metal anode with a thickness of 200 μm, denoted as K@FeSA-KZP / F-CNF composite anode material.

[0090] Comparative Example 1 The only difference between this comparative example and Example 2 is the removal of acetylacetone iron; otherwise, they are exactly the same. The specific steps are as follows: Step 1: Add 1.0g polyacrylonitrile, 0.25g polymethyl methacrylate and 0.1g zirconium oxynitrate to 9mL N,N-dimethylformamide and stir at 70℃ for 10h to obtain spinning solution.

[0091] Step 2: Electrospin the obtained spinning solution with a spinning voltage of 15 kV, a receiving distance of 15 cm, and a feed rate of 0.8 mL / h to obtain a polymer nanofiber membrane.

[0092] Step 3: After cutting the above nanofiber membrane into pieces with an average fragment size of 1 mm, disperse the nanofiber membrane and mixed solvent in a mixed solvent of 20 mL deionized water and 80 mL tert-butanol at a ratio of 1 g: 100 mL. Then, shear the mixture at high speed at 10000 rpm for 40 min to obtain a fiber slurry. Pour the fiber slurry into a cylindrical mold and freeze it at -60℃ for 6 h. Then, freeze-dry it at -70℃ and 10 Pa vacuum for 24 h to obtain a three-dimensional fiber aerogel.

[0093] Step 4: Pre-oxidize the three-dimensional fiber aerogel in air at 260℃ for 2 h, and then carbonize it at 900℃ for 3 h under an argon atmosphere to obtain nitrogen-doped carbon nanofiber aerogel.

[0094] Step 5: The obtained nitrogen-doped carbon nanofiber aerogel was immersed in a mixed solution containing 0.05 mol / L potassium dihydrogen phosphate and 0.02 mol / L citric acid at a ratio of 1 g: 100 mL. The aerogel was vacuum-impregnated for 20 min at 25 °C and 0.10 MPa. The impregnated carbon aerogel was then vacuum-dried for 8 h at 70 °C and 0.09 MPa, and then treated at 500 °C for 4 h under an argon atmosphere to obtain a composite carbon aerogel loaded with KZr2(PO4)3.

[0095] Step 6: Place the above-mentioned composite carbon aerogel in a plasma reaction chamber, use carbon tetrafluoride as the fluorine source, and process it at 80W power for 30 minutes. The carbon tetrafluoride flow rate is 40 sccm, the sample stage temperature is 20℃, and the sample temperature is kept below 60℃ by circulating water cooling during the process, thus obtaining KZP / F-CNF carbon-based framework material with a carbon tetrafluoride protective layer.

[0096] Step 7: In an argon glove box, metallic potassium is heated to 90°C to form molten potassium. The molten potassium is then dropped onto the surface of the KZP / F-CNF carbon-based framework material. The mass ratio of molten potassium to KZP / F-CNF carbon-based framework material is 3:1. The material is kept in contact for 15 minutes to allow the molten potassium to spontaneously infuse into the carbon aerogel. After cooling, the material is rolled into a composite potassium metal anode with a thickness of 160 μm, denoted as K@KZP / F-CNF composite anode material.

[0097] Comparative Example 2 The only difference between this comparative example and Example 2 is that ferric acetylacetone is replaced with an equal amount of ferric chloride; otherwise, the steps are exactly the same. Step 1: Add 1.0g polyacrylonitrile, 0.25g polymethyl methacrylate, 0.1g ferric chloride and 0.1g zirconium oxynitrate to 9mL N,N-dimethylformamide and stir at 70℃ for 10h to obtain spinning solution.

[0098] Step 2: Electrospin the obtained spinning solution with a spinning voltage of 15 kV, a receiving distance of 15 cm, and a feed rate of 0.8 mL / h to obtain a polymer nanofiber membrane.

[0099] Step 3: After cutting the above nanofiber membrane into pieces with an average fragment size of 1 mm, disperse the nanofiber membrane and mixed solvent in a mixed solvent of 20 mL deionized water and 80 mL tert-butanol at a ratio of 1 g: 100 mL. Then, shear the mixture at high speed at 10000 rpm for 40 min to obtain a fiber slurry. Pour the fiber slurry into a cylindrical mold and freeze it at -60℃ for 6 h. Then, freeze-dry it at -70℃ and 10 Pa vacuum for 24 h to obtain a three-dimensional fiber aerogel.

[0100] Step 4: Pre-oxidize the three-dimensional fiber aerogel in air at 260℃ for 2 h, and then carbonize it at 900℃ for 3 h under an argon atmosphere to obtain nitrogen-doped carbon nanofiber aerogel.

[0101] Step 5: The obtained nitrogen-doped carbon nanofiber aerogel was immersed in a mixed solution containing 0.05 mol / L potassium dihydrogen phosphate and 0.02 mol / L citric acid at a ratio of 1 g: 100 mL. The aerogel was vacuum-impregnated for 20 min at 25 °C and 0.10 MPa. The impregnated carbon aerogel was then vacuum-dried for 8 h at 70 °C and 0.09 MPa, and then treated at 500 °C for 4 h under an argon atmosphere to obtain a composite carbon aerogel loaded with KZr2(PO4)3.

[0102] Step 6: Place the above-mentioned composite carbon aerogel in a plasma reaction chamber, use carbon tetrafluoride as the fluorine source, and treat it at 80W power for 30 minutes. The carbon tetrafluoride flow rate is 40 sccm, the sample stage temperature is 20℃, and the sample temperature is kept below 60℃ by circulating water cooling during the treatment process, so as to obtain Fe-KZP / F-CNF carbon-based framework material with a carbon tetrafluoride protective layer.

[0103] Step 7: In an argon glove box, metallic potassium is heated to 90°C to form molten potassium. The molten potassium is then dropped onto the surface of the Fe-KZP / F-CNF carbon-based framework material. The mass ratio of molten potassium to Fe-KZP / F-CNF carbon-based framework material is 3:1. The material is kept in contact for 15 minutes to allow the molten potassium to spontaneously infuse into the carbon aerogel. After cooling, the material is rolled into a composite potassium metal anode with a thickness of 160 μm, denoted as K@Fe-KZP / F-CNF composite anode material.

[0104] Comparative Example 3 The only difference between this comparative example and Example 2 is the omission of the high-speed shearing step in step 3; the rest are identical, specifically including the following steps: Step 1: Add 1.0g polyacrylonitrile, 0.25g polymethyl methacrylate, 0.1g iron acetylacetone and 0.1g zirconium oxynitrate to 9mL N,N-dimethylformamide and stir at 70℃ for 10h to obtain spinning solution.

[0105] Step 2: Electrospin the obtained spinning solution with a spinning voltage of 15 kV, a receiving distance of 15 cm, and a feed rate of 0.8 mL / h to obtain a polymer nanofiber membrane.

[0106] Step 3: After cutting the above nanofiber membrane into pieces with an average fragment size of 1 mm, disperse the nanofiber membrane and mixed solvent in a mixed solvent of 20 mL deionized water and 80 mL tert-butanol at a ratio of 1 g: 100 mL to obtain a fiber slurry; pour the fiber slurry into a cylindrical mold, freeze it at -60℃ for 6 h, and then freeze-dry it at -70℃ and 10 Pa vacuum for 24 h to obtain a three-dimensional fiber aerogel.

[0107] Step 4: Pre-oxidize the three-dimensional fiber aerogel in air at 260℃ for 2 h, and then carbonize it at 900℃ for 3 h under an argon atmosphere to obtain nitrogen-doped carbon nanofiber aerogel.

[0108] Step 5: The obtained nitrogen-doped carbon nanofiber aerogel was immersed in a mixed solution containing 0.05 mol / L potassium dihydrogen phosphate and 0.02 mol / L citric acid at a ratio of 1 g: 100 mL. The aerogel was vacuum-impregnated for 20 min at 25 °C and 0.10 MPa. The impregnated carbon aerogel was then vacuum-dried for 8 h at 70 °C and 0.09 MPa, and then treated at 500 °C for 4 h under an argon atmosphere to obtain a composite carbon aerogel loaded with KZr2(PO4)3.

[0109] Step 6: Place the above-mentioned composite carbon aerogel in a plasma reaction chamber, use carbon tetrafluoride as the fluorine source, and treat it at 80W power for 30 minutes. The carbon tetrafluoride flow rate is 40 sccm, the sample stage temperature is 20℃, and the sample temperature is kept below 60℃ by circulating water cooling during the treatment process, so as to obtain FeSA-KZP / F-CNF carbon-based framework material with a carbon tetrafluoride protective layer.

[0110] Step 7: In an argon glove box, metallic potassium is heated to 90°C to form molten potassium. The molten potassium is then dropped onto the surface of the FeSA-KZP / F-CNF carbon-based framework material. The mass ratio of molten potassium to FeSA-KZP / F-CNF carbon-based framework material is 3:1. The contact is maintained for 15 minutes to allow the molten potassium to spontaneously infuse into the carbon aerogel. After cooling, the material is rolled into a composite potassium metal anode with a thickness of 160 μm, denoted as K@FeSA-KZP / F-CNF composite anode material.

[0111] Comparative Example 4 The only difference between this comparative example and Example 2 is the removal of the plasma treatment step; the rest are exactly the same. The specific steps are as follows: Step 1: Add 1.0g polyacrylonitrile, 0.25g polymethyl methacrylate, 0.1g iron acetylacetone and 0.1g zirconium oxynitrate to 9mL N,N-dimethylformamide and stir at 70℃ for 10h to obtain spinning solution.

[0112] Step 2: Electrospin the obtained spinning solution with a spinning voltage of 15 kV, a receiving distance of 15 cm, and a feed rate of 0.8 mL / h to obtain a polymer nanofiber membrane.

[0113] Step 3: After cutting the above nanofiber membrane into pieces with an average fragment size of 1 mm, disperse the nanofiber membrane and mixed solvent in a mixed solvent of 20 mL deionized water and 80 mL tert-butanol at a ratio of 1 g: 100 mL. Then, shear the mixture at high speed at 10000 rpm for 40 min to obtain a fiber slurry. Pour the fiber slurry into a cylindrical mold and freeze it at -60℃ for 6 h. Then, freeze-dry it at -70℃ and 10 Pa vacuum for 24 h to obtain a three-dimensional fiber aerogel.

[0114] Step 4: Pre-oxidize the three-dimensional fiber aerogel in air at 260℃ for 2 h, and then carbonize it at 900℃ for 3 h under an argon atmosphere to obtain nitrogen-doped carbon nanofiber aerogel.

[0115] Step 5: The obtained nitrogen-doped carbon nanofiber aerogel was immersed in a mixed solution containing 0.05 mol / L potassium dihydrogen phosphate and 0.02 mol / L citric acid at a ratio of 1 g: 100 mL. The aerogel was vacuum-impregnated for 20 min at 25 °C and 0.10 MPa. The impregnated carbon aerogel was then vacuum-dried for 8 h at 70 °C and 0.09 MPa, and then treated at 500 °C for 4 h under an argon atmosphere to obtain a composite carbon aerogel loaded with KZr2(PO4)3.

[0116] Step 6: In an argon glove box, metallic potassium is heated to 90°C to form molten potassium. The molten potassium is then dropped onto the surface of a composite carbon aerogel loaded with KZr2(PO4)3. The mass ratio of molten potassium to the composite carbon aerogel loaded with KZr2(PO4)3 is 3:1. The contact is maintained for 15 minutes to allow the molten potassium to spontaneously infuse into the carbon aerogel. After cooling, the aerogel is rolled into a composite potassium metal anode with a thickness of 160 μm, denoted as K@FeSA-KZP / CNF composite anode material.

[0117] Comparative Example 5 The only difference between this comparative example and Example 2 is the removal of zirconium oxynitrate; otherwise, they are identical, specifically including the following steps: Step 1: Add 1.0g polyacrylonitrile, 0.25g polymethyl methacrylate, and 0.1g ferric acetylacetone to 9mL of N,N-dimethylformamide and stir at 70℃ for 10h to obtain the spinning solution.

[0118] Step 2: Electrospin the obtained spinning solution with a spinning voltage of 15 kV, a receiving distance of 15 cm, and a feed rate of 0.8 mL / h to obtain a polymer nanofiber membrane.

[0119] Step 3: After cutting the above nanofiber membrane into pieces with an average fragment size of 1 mm, disperse the nanofiber membrane and mixed solvent in a mixed solvent of 20 mL deionized water and 80 mL tert-butanol at a ratio of 1 g: 100 mL. Then, shear the mixture at high speed at 10000 rpm for 40 min to obtain a fiber slurry. Pour the fiber slurry into a cylindrical mold and freeze it at -60℃ for 6 h. Then, freeze-dry it at -70℃ and 10 Pa vacuum for 24 h to obtain a three-dimensional fiber aerogel.

[0120] Step 4: Pre-oxidize the three-dimensional fiber aerogel in air at 260℃ for 2 h, and then carbonize it at 900℃ for 3 h under an argon atmosphere to obtain nitrogen-doped carbon nanofiber aerogel.

[0121] Step 5: The obtained nitrogen-doped carbon nanofiber aerogel was immersed in a mixed solution containing 0.05 mol / L potassium dihydrogen phosphate and 0.02 mol / L citric acid at a ratio of 1 g: 100 mL. The aerogel was vacuum-impregnated for 20 min at 25 °C and 0.10 MPa. The impregnated carbon aerogel was then vacuum-dried for 8 h at 70 °C and 0.09 MPa, and then treated at 500 °C for 4 h under an argon atmosphere to obtain a composite carbon aerogel.

[0122] Step 6: Place the above-mentioned composite carbon aerogel in a plasma reaction chamber, use carbon tetrafluoride as the fluorine source, and treat it at 80W power for 30 minutes. The carbon tetrafluoride flow rate is 40 sccm, the sample stage temperature is 20℃, and the sample temperature is kept below 60℃ by circulating water cooling during the treatment process, so as to obtain FeSA / F-CNF carbon-based framework material with a carbon tetrafluoride protective layer.

[0123] Step 7: In an argon glove box, metallic potassium is heated to 90°C to form molten potassium. The molten potassium is then dropped onto the surface of the FeSA / F-CNF carbon-based framework material. The mass ratio of molten potassium to FeSA / F-CNF carbon-based framework material is 3:1. The contact is maintained for 15 minutes to allow the molten potassium to spontaneously infuse into the carbon aerogel. After cooling, the material is rolled into a composite potassium metal anode with a thickness of 160 μm, denoted as K@FeSA / F-CNF composite anode material.

[0124] Comparative Example 6 The only difference between this comparative example and Example 2 is that zirconium oxynitrate is replaced with zirconium oxide nanoparticles; otherwise, the steps are exactly the same. The specific steps are as follows: Step 1: Add 1.0g polyacrylonitrile, 0.25g polymethyl methacrylate, 0.1g iron acetylacetone and 0.1g zirconium oxide to 9mL N,N-dimethylformamide and stir at 70℃ for 10h to obtain spinning solution.

[0125] Step 2: Electrospin the obtained spinning solution with a spinning voltage of 15 kV, a receiving distance of 15 cm, and a feed rate of 0.8 mL / h to obtain a polymer nanofiber membrane.

[0126] Step 3: After cutting the above nanofiber membrane into pieces with an average fragment size of 1 mm, disperse the nanofiber membrane and mixed solvent in a mixed solvent of 20 mL deionized water and 80 mL tert-butanol at a ratio of 1 g: 100 mL. Then, shear the mixture at high speed at 10000 rpm for 40 min to obtain a fiber slurry. Pour the fiber slurry into a cylindrical mold and freeze it at -60℃ for 6 h. Then, freeze-dry it at -70℃ and 10 Pa vacuum for 24 h to obtain a three-dimensional fiber aerogel.

[0127] Step 4: Pre-oxidize the three-dimensional fiber aerogel in air at 260℃ for 2 h, and then carbonize it at 900℃ for 3 h under an argon atmosphere to obtain nitrogen-doped carbon nanofiber aerogel.

[0128] Step 5: The obtained nitrogen-doped carbon nanofiber aerogel was immersed in a mixed solution containing 0.05 mol / L potassium dihydrogen phosphate and 0.02 mol / L citric acid at a ratio of 1 g: 100 mL. The aerogel was vacuum-impregnated for 20 min at 25 °C and 0.10 MPa. The impregnated carbon aerogel was then vacuum-dried for 8 h at 70 °C and 0.09 MPa, and then treated at 500 °C for 4 h under an argon atmosphere to obtain a composite carbon aerogel.

[0129] Step 6: Place the above-mentioned composite carbon aerogel in a plasma reaction chamber, use carbon tetrafluoride as the fluorine source, and process it at 80W power for 30 minutes. The carbon tetrafluoride flow rate is 40 sccm, the sample stage temperature is 20℃, and the sample temperature is kept below 60℃ by circulating water cooling during the process, thus obtaining a carbon-based skeleton material with a fluorinated carbon protective layer.

[0130] Step 7: In an argon glove box, metallic potassium is heated to 90°C to form molten potassium. The molten potassium is then dropped onto the surface of the carbon-based framework material. The mass ratio of molten potassium to the carbon-based framework material is 3:1. The contact is maintained for 15 minutes to allow the molten potassium to spontaneously infuse into the carbon aerogel. After cooling, the material is rolled into a composite potassium metal anode with a thickness of 160 μm, denoted as K@FeSA-ZrO2 / F-CNF composite anode material.

[0131] Application Examples The composite materials prepared in Examples 1-4 and Comparative Examples 1-6 were used to assemble potassium-sulfur batteries, and their capacity, initial coulombic efficiency, and long-cycle capacity retention were tested. The specific steps are as follows: Electrode preparation: Commercial sulfur (density 2.1 g / cm³) was used. 3 Specific surface area 20m² 2 Acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 7:2:1 to form a slurry, which was then uniformly coated onto the surface of aluminum foil, with the coating amount controlled at 2.5 mg / cm³. 2 The electrode was vacuum dried at 80℃ for 12 hours. The dried electrode was then cut into circular electrode sheets with a diameter of 12 mm.

[0132] Battery assembly: Using the composite material obtained in this invention as the negative electrode, the electrode prepared in the above steps as the positive electrode, glass fiber as the separator, and 1.0 M potassium difluorosulfonyl imide in ethylene glycol dimethyl ether solution as the electrolyte, CR2032 coin cells are assembled in an argon glove box.

[0133] Electrochemical testing: The assembled battery was placed on the Land CT2001A battery testing system. The test temperature was kept constant at 25℃ and the voltage window was 0.5~3.0V. Constant current charge-discharge tests were performed at current densities of 30mA / g and 5A / g, respectively. The capacity of the cathode material, the initial coulombic efficiency, and the long-cycle capacity retention rate were recorded.

[0134] The test results are shown in Table 1 and Figures 6-7 As shown.

[0135] Table 1. Electrochemical data of the corresponding potassium-sulfur battery cathode materials when the samples prepared in Examples 1-4 and Comparative Examples 1-6 are used as negative electrodes. As shown in Table 1, when the potassium metal composite materials prepared in Examples 1 to 4 are used as the negative electrode of potassium-sulfur batteries, the initial discharge specific capacity of the sulfur positive electrode at a current density of 30 mA / g all reach above 1122 mAh / g, and the initial coulombic efficiency is between 94.1% and 94.7%. After cycling 1000 times at a high current density of 5 A / g, the specific capacity still remains above 925 mAh / g, and the capacity retention rate reaches 90.5% to 91.5%. This indicates that the potassium metal composite material prepared in the examples of the present invention helps the sulfur positive electrode achieve high reversible capacity, excellent rate performance and long cycle stability.

[0136] Comparative Example 1, without the addition of iron acetylacetone, lacked Fe-N4 single-atom sites in the carbon matrix after carbonization. The initial specific capacity of the sulfur cathode material decreased to 802.0 mAh / g, with an initial coulombic efficiency of only 75.2%. After 1000 cycles at 5 A / g, the specific capacity decayed to 465.0 mAh / g, with a capacity retention of 71.5%. The absence of Fe-N4 single-atom sites significantly reduced the uniform nucleation ability of potassium, exacerbated the corrosion of potassium metal by polysulfides and the potassium dendrite problem, resulting in a significant reduction in capacity and cycle life.

[0137] Comparative Example 2 used ferric chloride instead of ferric acetylacetone. Ferric chloride is an inorganic salt, which has poor dispersibility in spinning solution and weak coordination with polyacrylonitrile. After carbonization, iron species easily agglomerate to form metallic iron or iron carbide nanoparticles, making it difficult to form Fe-N4 single atoms. The sulfur cathode material had an initial specific capacity of 840.7 mAh / g and an initial coulombic efficiency of 78.5%. After cycling, the specific capacity was 530.4 mAh / g, and the capacity retention was 75.4%. Although slightly better than Comparative Example 1, which was completely iron-free, it was far lower than the examples, indicating that the type of iron source is crucial to the formation of Fe-N4 single atoms. Ferric acetylacetone, as an organometallic complex, is more conducive to the formation of single-atom sites.

[0138] Comparative Example 3 omitted the high-speed shearing step, and the fiber membrane was freeze-dried without sufficient dispersion. The resulting material exhibited uneven fiber distribution and an incomplete three-dimensional interconnected network structure. The initial specific capacity of the sulfur cathode material was only 772.7 mAh / g, the lowest among all samples, with an initial coulombic efficiency of 74.5%. After 1000 cycles at 5 A / g, the specific capacity decreased to 345.2 mAh / g, with a capacity retention of only 62.7%. This indicates that high-speed shearing is indispensable for forming a uniform fiber slurry and a three-dimensional interconnected porous framework. The structural inhomogeneity hinders electron and ion transport, increases local current density, and leads to severe structural degradation during cycling.

[0139] Comparative Example 4 lacked carbon tetrafluoride plasma treatment, resulting in a missing fluorinated carbon protective layer on the material's outer surface. The initial coulombic efficiency of the sulfur cathode material was only 71.2%, the lowest among all samples. After 1000 cycles at 5 A / g, the capacity retention was only 54.9%, also the lowest among all samples. The absence of the fluorinated carbon protective layer led to instability at the solid electrolyte interface, continuous electrolyte decomposition, and persistent erosion of the potassium anode by potassium polysulfides, resulting in low coulombic efficiency and rapid capacity decay.

[0140] Comparative Example 5, without the addition of zirconium oxynitrate, lacked zirconium species in its carbon framework after carbonization, making it impossible to generate the KZr2(PO4)3 fast-conducting phase in subsequent steps. The initial specific capacity of the sulfur cathode material was 859.3 mAh / g, with an initial coulombic efficiency of 79.4%. After cycling, the specific capacity was 415.8 mAh / g, and the capacity retention was 67.5%. The absence of the potassium ion fast-conducting phase reduced the migration rate of potassium ions within the electrode and increased polarization under high current, leading to a significant decrease in both rate performance and cycle stability.

[0141] Comparative Example 6 uses zirconium oxide instead of zirconium oxynitrate. Zirconia is a crystalline oxide that cannot dissolve in the spinning solution and is physically encapsulated within the polymer fiber as solid particles. During subsequent carbonization, the volume and phase of the zirconium oxide particles remain essentially unchanged. Unlike the liquid precursor zirconium oxynitrate, it cannot undergo thermal decomposition and phase transition-induced volume shrinkage. Therefore, it cannot generate nanocavities in situ within the carbon fiber to buffer the volume expansion of potassium deposition. These spaces occupied by zirconium oxide particles become stress concentration sites rather than buffer regions during cycling, which is detrimental to the long-term maintenance of the electrode structure. Furthermore, its high chemical stability makes it difficult to fully react with phosphate ions to convert to KZr2(PO4)3 during subsequent heat treatment, leaving unreacted insulating zirconium oxide phase. The sulfur cathode material exhibits an initial specific capacity of 885.8 mAh / g, an initial coulombic efficiency of 80.0%, and a post-cycle specific capacity of 520.9 mAh / g with a capacity retention of 75.2%. While slightly better than Comparative Example 5 without zirconium, it still shows a significant difference compared to the examples. This indicates that the chemical morphology of the zirconium source directly affects the in-situ formation of KZr2(PO4)3 and the formation of the carbon framework pore structure.

[0142] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3, characterized in that, The invention comprises a three-dimensional interconnected porous framework of nitrogen-doped carbon nanofibers, wherein Fe-N4 single atoms are dispersed in the carbon matrix of the nitrogen-doped carbon nanofibers; KZr2(PO4)3 nanoparticles are loaded on the surface and in the pores of the nitrogen-doped carbon nanofibers; and the outer surface of the nitrogen-doped carbon nanofibers is coated with a fluorinated carbon protective layer; and the pores of the porous framework of nitrogen-doped carbon nanofibers are also filled with metallic potassium.

2. The method for preparing the iron single-atom / KZr2(PO4)3 co-modified carbon-based composite material according to claim 1, characterized in that, Includes the following steps: Step a: Polyacrylonitrile, pore-forming agent, iron acetylacetone and zirconium oxynitrate are added to an organic solvent and mixed evenly to obtain a spinning solution; the spinning solution is electrospun to obtain a nanofiber membrane. Step b: Disperse the nanofiber membrane in an alcohol-water solution and shear it at high speed to obtain a fiber slurry; The fiber slurry was freeze-dried to obtain a three-dimensional fiber aerogel; Step c: The three-dimensional fiber aerogel is subjected to pre-oxidation and carbonization treatments in sequence to obtain nitrogen-doped carbon nanofibers; Step d: The nitrogen-doped carbon nanofibers are added to a mixed solution containing potassium source, phosphorus source and citric acid for vacuum impregnation, dried and then heat-treated under an inert atmosphere to cause Zr to undergo an in-situ phosphate reaction with potassium source and phosphate to obtain nitrogen-doped carbon nanofibers loaded with KZr2(PO4)3. Step e: The nitrogen-doped carbon nanofibers loaded with KZr2(PO4)3 are placed in a plasma reaction chamber and subjected to plasma treatment with carbon tetrafluoride as a fluorine source to form a fluorinated carbon protective layer on the surface, thereby obtaining a three-dimensional carbon-based support. Step f: Then, under an inert atmosphere, molten potassium metal is brought into contact with the three-dimensional carbon-based support, allowing the molten potassium to penetrate into its porous framework, resulting in a carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3.

3. The method for preparing the iron single-atom / KZr2(PO4)3 co-modified carbon-based composite material as described in claim 2, characterized in that, In step a, the pore-forming agent is at least one of polyvinylpyrrolidone, polymethyl methacrylate, polyethylene glycol, or polystyrene; and / or In step a, the organic solvent is N,N-dimethylformamide; and / or In step a, the mass ratio of polyacrylonitrile to pore-forming agent is 3:1 to 4:1; and / or In step a, the amount of acetylacetone iron added is 1% to 10% of the mass of polyacrylonitrile; and / or In step a, the amount of zirconium oxynitrate added is 2% to 15% of the mass of polyacrylonitrile; and / or In step a, the mass concentration of polyacrylonitrile in the spinning solution is 8%~15%; and / or In step a, the mixing temperature is 60℃~80℃, and the mixing time is 6h~12h; and / or In step a, the voltage of the electrospinning is 15kV~25kV, the receiving distance is 15cm~20cm, and the advancing speed is 0.5mL / h~2mL / h.

4. The method for preparing the iron single-atom / KZr2(PO4)3 co-modified carbon-based composite material as described in claim 2, characterized in that, In step b, the nanofiber membrane is first sheared to an average fragment size of 0.5 mm to 5 mm before dispersion; and / or In step b, the alcohol-water solution is a mixed solution of deionized water and tert-butanol with a volume ratio of 1:1 to 1:4; and / or In step b, the mass-to-volume ratio of the nanofiber membrane to the alcohol-water solution is 1g:100mL to 1g:300mL; and / or In step b, the high-speed shearing rotation speed is 8000 rpm to 15000 rpm, and the high-speed shearing time is 20 min to 60 min; and / or In step b, the specific steps of freeze drying include: first freezing at -20℃ to -80℃ for 4h to 12h, and then vacuum freezing at -50℃ to -80℃ and 5Pa to 15Pa for 24h to 48h.

5. The method for preparing the iron single-atom / KZr2(PO4)3 co-modified carbon-based composite material as described in claim 2, characterized in that, In step c, the pre-oxidation temperature is 220℃~280℃, and the pre-oxidation time is 2h~3h; and / or In step c, the carbonization temperature is 900℃~1000℃ and the carbonization time is 2h~3h.

6. The method for preparing the iron single-atom / KZr2(PO4)3 co-modified carbon-based composite material as described in claim 2, characterized in that, In step d, the mixed solution is an aqueous solution containing 0.05 mol / L to 0.20 mol / L potassium dihydrogen phosphate and 0.02 mol / L to 0.10 mol / L citric acid; the mass-to-volume ratio of the nitrogen-doped carbon nanofibers to the mixed solution is 1 g:50 mL to 1 g:200 mL; and / or Step d, the vacuum impregnation temperature is 20℃~30℃, the vacuum degree is 0.08MPa~0.10MPa, and the impregnation time is 10min~40min; and / or In step d, the heat treatment temperature is 500℃~600℃, and the heat treatment time is 2h~4h.

7. The method for preparing the iron single-atom / KZr2(PO4)3 co-modified carbon-based composite material as described in claim 2, characterized in that, In step e, the plasma treatment power is 80W~150W, the treatment time is 10min~30min, and the carbon tetrafluoride flow rate is 10sccm~40sccm; and / or In step f, the mass ratio of the molten potassium to the three-dimensional carbon-based support is 1.5:1 to 4:

1.

8. A negative electrode, characterized in that, The carbon-based composite material including the iron single atom / KZr2(PO4)3 co-modified material as described in claim 1.

9. A potassium-sulfur battery, characterized in that, Including the carbon-based composite material co-modified with iron single atoms / KZr2(PO4)3 as described in claim 1 or the negative electrode as described in claim 8.

10. A battery module, characterized in that, Including the potassium-sulfur battery as described in claim 9.